Future Changes in Seasonality of the North Pacific and North Atlantic Subtropical Highs. Issue 21 (12th November 2018) - Song, Fengfei; Leung, L. Ruby; Lu, Jian; Dong, Lu
Abstract: The subtropical highs have a zonal mean and a zonally asymmetric component related to the Hadley cell and land‐sea contrast, respectively. Based on 37 Coupled Model Intercomparison Project phase 5 models, relative roles of the Hadley cell and land‐sea contrast in future changes of the North Pacific and North Atlantic subtropical highs (NPSH and NASH) are evaluated. Both the NPSH and NASH are significantly enhanced during boreal spring (April–June) but not in summer (July–September). Although the zonally asymmetric component contributes to more than half of the enhancement during spring, the zonal mean component is responsible for the interseasonal contrast of the responses of the NPSH and NASH between spring and summer. The seasonally dependent Hadley cell changes are due to changes in tropical precipitation related to sea surface temperature (SST) warming, while enhanced land‐sea contrast has comparable effects on the NPSH and NASH during both spring and summer, with important implications to U.S. regional precipitation. Plain Language Summary: The North Pacific and North Atlantic subtropical highs (NPSH and NASH) are the most evident low‐level atmospheric features in the Northern Hemisphere during the warm season (April–September). Both the Hadley cell and land‐sea distribution contribute to its formation and seasonal variation. Previous studies only focused on the future changes of the NPSH and NASH during their peak season (June–August). Here we found that both the NPSH and NASH will be intensified more during spring (April–June) than summer (July–September) under climate warming. The enhanced land‐sea thermal contrast under global warming strengthens the NPSH and NASH, with similar magnitude in spring and summer. However, the Hadley cell enhances the NPSH and NASH during spring while weakens them during summer. Hence, the seasonally dependent response of the NPSH and NASH is mainly driven by the Hadley cell. The seasonality changes of the NPSH and NASH have important implications for the U.S. regional precipitation. Key Points: Both North Pacific and North Atlantic subtropical highs are more significantly enhanced during spring than summer in response to warming Land‐sea contrast contributes more to the enhancement in spring, but the Hadley cell dominates the seasonally dependent response The spring enhancement and seasonal dependence of subtropical high response have important implications for U.S. regional precipitation